1992
DOI: 10.1136/gut.33.8.1042
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between echographic gastric emptying and appetite: influence of psyllium.

Abstract: The correlation between ultrasonographic gastric emptying and appetite was studied. Echographic evaluation of gastric emptying by measurement of the antral vertical diameter and assessment of sensations of hunger and satiety using analogue visual scales were performed simultaneously in 12 healthy volunteers. Measurements were carried out after the intake of 10O8 g psyilium or placebo in a randomised, crossover, double blind trial. The correlation between echographic gastric emptying and sensations of hunger an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
88
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(97 citation statements)
references
References 5 publications
4
88
1
4
Order By: Relevance
“…Several studies have used nutritional, physical or pharmacological interventions which delayed gastric emptying rates in healthy subjects. [27][28][29][30][31][32][33][34][35][36] Although not specifically designed to evaluate changes in meal-related symptoms, none of these studies reported the induction of dyspepsia-like symptoms in the participants.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used nutritional, physical or pharmacological interventions which delayed gastric emptying rates in healthy subjects. [27][28][29][30][31][32][33][34][35][36] Although not specifically designed to evaluate changes in meal-related symptoms, none of these studies reported the induction of dyspepsia-like symptoms in the participants.…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, the results of many studies conducted on humans showed that psyllium reduces caloric consumption while improving satiety. [28][29][30] The action of psyllium on caloric intake and satiety could result from its capacity to increase chyme viscosity, which slows down gastric emptying, as shown previously in humans 28 and dogs. 31 To assess the relative effects of both fiber and protein supplementation most appropriately, 4 similarly formulated diets would have been needed, which only differed in fiber and protein content (eg, HPHF, HP only, HF only, and neither HP nor HF).…”
Section: Discussionmentioning
confidence: 99%
“…Kovacs et al (2001) found that a drink containing guar gum reduced hunger and Bergmann et al (1992) found increasing the viscosity of a liquid meal with psyllium increases a person's level of satiety supporting the effect of high water foods in satiety.…”
Section: Discussionmentioning
confidence: 99%